Electrophysiological and Behavioral Responses of Batocera horsfieldi Hope to Volatiles from Pistacia chinensis Bunge - Jianting Fan; Kaiwen Zheng; Ping Xie; Yifan Dong; Yutong Gu; Jacob D. Wickham (Insects, 2023)
Following infestation by phytophagous insects, changes in the composition and relative proportion of volatile components emitted by plants may be observed. Some phytophagous insects can accurately identify these compounds to locate suitable host plants. We investigated whether herbivore-induced plant volatiles (HIPVs) generated by herbivory on Pistacia chinensis Bunge (Sapindales: Aceraceae) might be semiochemicals for the host location of Batocera horsfieldi Hope (Coleoptera: Cerambycidae). We performed two-choice bioassays (indoor darkroom, inside cages) on plants damaged by adult feeding and intact control plants. Volatiles from these plants were then collected and identified, and the response of adult antennae to these compounds was tested via electroantennography (EAG). The behavioral responses of B. horsfieldi to these compounds were finally assessed using a Y-tube olfactometer. Host plant choice tests show that B. horsfieldi prefers feeding-damaged P. chinensis over healthy trees. In total, 15 compounds were collected from healthy and feeding-damaged P. chinensis, 10 of which were shared in both healthy and feeding-damaged P. chinensis, among which there were significant differences in the quantities of five terpenes, including α-pinene, β-pinene, α-phellandrene, D-limonene, and β-ocimene. In EAG assays, the antennae of B. horsfieldi adults responded strongly to (Z)-3-hexen-1-ol, β-ocimene, 3-carene, γ-terpinene, D-limonene, myrcene, and α-phellandrene. The antennae of B. horsfieldi adults responded in a dose–response manner to these compounds. Y-tube behavioral experiments showed that four compounds attracted mated females ((Z)-3-hexen-1-ol, β-ocimene, 3-carene, and α-phellandrene), two compounds ((Z)-3-hexen-1-ol and α-phellandrene) attracted males, and adults of both sexes avoided D-limonene. Feeding bioassays showed that (Z)-3-hexen-1-ol and β-ocimene could promote the feeding of B. horsfieldi and that D-limonene inhibited this response. These results could provide a theoretical basis for developing attractants or repellents for B. horsfieldi.